Impact of Personality Traits on Entrepreneurial Intentions of University Students - Ishfaq Ahmed; Muhammad Ramzan; Muhammad Usman (JISR Management and Social Sciences & Economics, 2010)
In the hard times when educated persons can not get a job, self employment is referred as the solution. But entrepreneurship is not the function that might be outcome of simple efforts. It requires a regular and permanent attitude as part of personality. This research aims to study the impact of personal traits on entrepreneurial intentions of university students. Two individual personality traits were taken as predictor of entrepreneurial intentions, locus of control and self efficacy. Data was collected from the sample size of 276 university students. All of the students were in the final semesters of their studies. Results show strong relation between personal traits and entrepreneurial intentions. However some demographic characteristics like gender were insignificant with the intentions to become entrepreneurs, but prior experience, family exposure to business and entrepreneurial education have significant relation with intentions to become an entrepreneur.